2014
DOI: 10.3390/f5123274
|View full text |Cite
|
Sign up to set email alerts
|

Tree Root System Characterization and Volume Estimation by Terrestrial Laser Scanning and Quantitative Structure Modeling

Abstract: Abstract:The accurate characterization of three-dimensional (3D) root architecture, volume, and biomass is important for a wide variety of applications in forest ecology and to better understand tree and soil stability. Technological advancements have led to increasingly more digitized and automated procedures, which have been used to more accurately and quickly describe the 3D structure of root systems. Terrestrial laser scanners (TLS) have successfully been used to describe aboveground structures of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
2
18
1
Order By: Relevance
“…The average volume error for all models was below 5%, and using, e.g., the circular cylinder model on extremely elliptic stems, resulted in a maximum volume error below 14%. These ties well with the field-calibrated studies of [16,23], as the volume and length errors are similar in all studies. In [16], it is shown that a hybrid version of polyhedral and cylindrical modelling is accurate, even for the highly complex shapes of stump-root systems.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The average volume error for all models was below 5%, and using, e.g., the circular cylinder model on extremely elliptic stems, resulted in a maximum volume error below 14%. These ties well with the field-calibrated studies of [16,23], as the volume and length errors are similar in all studies. In [16], it is shown that a hybrid version of polyhedral and cylindrical modelling is accurate, even for the highly complex shapes of stump-root systems.…”
Section: Discussionsupporting
confidence: 65%
“…These ties well with the field-calibrated studies of [16,23], as the volume and length errors are similar in all studies. In [16], it is shown that a hybrid version of polyhedral and cylindrical modelling is accurate, even for the highly complex shapes of stump-root systems. Furthermore, [24] shows that using allometric equations to predict the volume of eucalyptus trees results in a 36.6% average error with the species-specific equation and a 29.9% error with the generic eucalyptus equation, while circular cylinder structure models produce an error of 9.7%.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, in addition to the regular tree attributes measured in practical field inventories, more detailed tree attributes, such as the stem curve or taper curve (stem diameter as a function of height), which reveal the wood productivity and quality, can be derived from TLS with high degrees of accuracy [9]. Studies have explored the use of TLS at the plot level for assessing stem volume and biomass components [10][11][12][13] for individual tree reconstruction, including branches, twigs, and leaves [3,14,15], in order to improve the physiological understanding of tree growth [16]. Moreover, TLS has been used for determining the stem curve [17,18], which is not easily measurable using conventional tools.…”
Section: Introductionmentioning
confidence: 99%